Wear-resistant self-lubricating copper-based friction material in high temperature environment and preparation method thereof
By adding Ni3Al and CeF3+Ag composite lubricating phases to high manganese aluminum bronze, the adhesion wear problem at high temperature is solved, the material's wear resistance and lubrication performance is improved, and the friction coefficient and wear rate are achieved.
Patent Information
- Application Number
- CN202410707454.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-03
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-06-03
AI Technical Summary
The adhesion wear effect of high manganese aluminum bronze is enhanced under high temperature conditions, resulting in an increase in wear rate and fluctuation in friction coefficient, and a decrease in service performance and life.
By simultaneously adding the reinforced phase Ni3Al and the composite lubricated phase (CeF3+Ag) to the copper matrix, and adjusting its ratio, it reduces the adhesion wear and wear of abrasive particles, and reduces the friction coefficient and wear rate.
It significantly improves the wear resistance and lubrication performance of copper-based friction materials, meets the requirements for use in high temperature environments, and reduces the friction coefficient and wear rate of the material.
Smart Images

Figure BDA0004873046340000071 
Figure BDA0004873046340000072 
Figure BDA0004873046340000081
Abstract
Description
Technical Field
[0001] The invention relates to a high-temperature environment wear-resistant self-lubricating copper-based friction material and a preparation method thereof, belonging to the technical field of copper-based composite friction materials. Background Art
[0002] High manganese aluminum bronze has excellent high-temperature oxidation resistance and corrosion resistance, and has relatively high strength and hardness among copper alloys. It has been widely used in sliding bearings, gears, copper sleeves, wet friction plates and other components. However, during the friction and wear process of this material under high-temperature conditions, the adhesive wear effect gradually increases, a large amount of material falls off and forms a transfer layer on the dual surface, resulting in an increase in wear rate and fluctuations in friction coefficient, and a significant decrease in performance and life. Therefore, the friction performance and wear mechanism of high manganese aluminum bronze at high temperatures need to be further improved.
[0003] In recent years, researchers have conducted in-depth research on the tribological properties of high manganese aluminum bronze materials. Patent CN112195361A improves the strength and wear resistance of aluminum bronze by adding elements such as Zn and Ti; Patent CN114892039A effectively improves the wear resistance and corrosion resistance of the material by increasing the Mn element content; Patent CN105088004A effectively reduces the wear rate of aluminum bronze by adding elements such as Cr and Si. However, the above patents mainly produce strengthening effects through mechanisms such as grain refinement and grain boundary strengthening, without adding strengthening phases and lubricating phases, and have limited effects on improving the lubrication performance and wear mechanism of the material in a high temperature environment. Patent CN108417435B reduces the wear rate and friction coefficient by adding graphene, carbon nanotubes and lead as lubricants in the copper matrix, but lead is not good for organisms and the environment, the direction of carbon nanotubes is difficult to accurately control, and the ability to limit the adhesive wear mechanism under high temperature conditions is insufficient. Therefore, if the adhesive wear effect of high manganese aluminum bronze can be effectively limited by optimizing the material formula and improving the preparation process, the comprehensive performance and service life of the material will be significantly improved.
[0004] Studies have shown that adding alloying elements to aluminum bronze alloys can improve hardness and strength, but there is no report on regulating the mechanical properties and wear resistance of aluminum bronze alloys by adjusting the content of Mn, Co, and B. 3 At high temperatures, a lubricating film will form on the friction surface, keeping the friction coefficient low and stable; Ag can reduce the damage of hard wear debris to the friction surface, thereby weakening the three-body wear mechanism. 3 The research and application of friction performance between CeF and Ag is still unknown. 3 The Ni-Ag composite was added to aluminum bronze and the coupling performance was precisely regulated. 3Al has higher hardness and wear resistance, and has stronger bonding strength with the aluminum bronze interface than the ceramic reinforcement phase. 3 Al and composite lubricating phase (CeF 3 +Ag) is added to aluminum bronze at the same time to take into account the research on lubrication and wear resistance. Summary of the invention
[0005] In view of this, the present invention provides a high temperature environment wear-resistant self-lubricating copper-based friction material and a preparation method thereof, by optimizing the composition and content of each component of the friction material, mainly by adding a reinforcing phase Ni 3 Al and composite lubricating phase (CeF 3 +Ag) to produce coupling effect, and by adjusting its ratio, Ni 3 Al weakens adhesive wear and (CeF 3 +Ag) to reduce the abrasive wear effect to reduce the friction coefficient and wear rate, so that the wear resistance and lubrication performance of the friction material are significantly improved to meet the requirements of use in high temperature environments; and the preparation method of the friction material is simple, the raw materials are environmentally friendly, the cost is low, and the economic benefit is high. It is suitable for friction parts such as sliding bearings, bushings, sliders in high temperature environments, and has broad application prospects.
[0006] The objectives of the present invention are achieved through the following technical solutions.
[0007] The wear-resistant self-lubricating copper-based friction material in a high-temperature environment, taking the total mass of the raw materials for preparing the friction material as 100%, the composition of the raw materials and the mass percentage of each component are as follows: 78-92% matrix phase, 3-10% reinforcement phase and 5-12% composite lubricating phase. The wear-resistant self-lubricating copper-based friction material in a high-temperature environment can be prepared by sintering the above components.
[0008] The matrix phase is high manganese aluminum bronze, and the strengthening phase is Ni 3 Al, the composite lubricating phase is CeF 3 and Ag complex.
[0009] Ordinary aluminum bronze is a copper-based alloy with aluminum as the main alloying element and other elements such as iron, manganese, and nickel. High manganese aluminum bronze has a higher manganese content than ordinary aluminum bronze. The mass percentage of manganese in the high manganese aluminum bronze described in the present application is 6-10%. Preferably, the composition of the high manganese aluminum bronze and the mass percentage of each component in the raw material for preparing the friction material are as follows: Cu 58-73%, Al 6-8%, Ni 1-2.5%, Fe 2-3%, Mn 6-10%, Co0.5-1%, and B 0.5-1.0%. More preferably, the powder particle size of each of the above components is 200-300 mesh.
[0010] Preferably, CeF in the composite lubricating phase 3 The mass ratio of Ag to Ag is 20:80-80:20; more preferably, the particle sizes of the two powders are both 200-300 meshes.
[0011] Preferably, the composite lubricating phase is CeF 3 The mixture is obtained by high-energy ball milling with Ag under inert gas protection, with a ball-to-material ratio of 3:1-4:1, a ball milling speed of 250-350 r / min, and a ball milling time of 8-10 h. More preferably, anhydrous ethanol is added before ball milling, and the ball milling is stopped every 5-10 min, and the ball milling is continued after stopping for 2-3 min. More preferably, the ball milling jar and the ball milling beads are made of WC-Co cemented carbide.
[0012] The preparation method of the wear-resistant self-lubricating copper-based friction material in a high-temperature environment comprises the following steps:
[0013] First, high manganese aluminum bronze, Ni 3 Al and the composite lubricating phase are mixed uniformly to obtain a mixed raw material; the mixed raw material is loaded into a sintering mold, and then placed in a sintering furnace for sintering to obtain the friction material.
[0014] Preferably, the mixed raw material is obtained by ball milling under an inert gas atmosphere, with a ball-to-material ratio of 1:1-3:1, a ball milling speed of 150-200 r / min, and a ball milling time of 6-9 h. More preferably, the ball milling jar and the ball milling beads are made of WC-Co cemented carbide.
[0015] Preferably, the sintering process parameters are as follows: hot pressing sintering is performed under a vacuum degree lower than 0.1 Pa, the sintering temperature is 850-910° C., the sintering pressure is 36-40 MPa, and the sintering heat and pressure holding time is 5-10 min.
[0016] Preferably, the heating rate during the sintering process is 110-170° C. / min.
[0017] Beneficial effects:
[0018] (1) The present invention uses high manganese aluminum bronze as the matrix phase, increases the manganese content compared to ordinary aluminum bronze, reduces the transformation temperature of the β phase, and inhibits the eutectoid decomposition of the β phase, thereby improving the strength of the aluminum bronze; the additionally added Co element promotes the formation of a hard and fine κ phase, thereby producing a grain refinement effect to enhance the strength of the high manganese aluminum bronze; the additionally added B element is dispersed in the high manganese aluminum bronze matrix to produce a dispersion strengthening effect. Compared with existing matrix strengthening technologies, the present invention strictly controls the content of Mn, Co and B, combines the solid solution strengthening effect with the dispersion strengthening effect, thereby improving the slip of dislocations on grain boundaries, and further improving the mechanical properties and wear resistance of the high manganese aluminum bronze matrix.
[0019] (2) The present invention uses Ni 3 Al as a strengthening phase and regulating its content improves the wear resistance of the high manganese aluminum bronze matrix. 2 O 3 Commonly used ceramic strengthening phases, Ni 3 Al has a stronger bonding force with the high manganese aluminum bronze matrix interface and can weaken the adhesive wear mechanism at high temperatures, so adding Ni 3 Aluminum bronze material of Al has excellent strength and wear resistance.
[0020] (3) The present invention uses CeF 3 The composite lubricating phase of CeF and Ag forms a stable separation film with low shear force on the high-temperature friction surface and reduces the damage of hard wear debris to the friction surface. 3 The relative content of CeF 3 Too much CeF and too little Ag will reduce the strength and wear resistance of the material due to decreased internal bonding and excessive grain boundary impurities. 3 Too little Ag or too much Ag makes it difficult to effectively improve the high temperature lubrication performance of the material. Compared with materials with commonly used lubricating phases such as graphite, the present invention can improve the high temperature lubrication performance of the material by accurately adjusting the CeF 3 +Ag) composition ratio, which improves the lubrication performance under high temperature and room temperature conditions.
[0021] (4) The present invention provides a high temperature environment wear-resistant self-lubricating friction material by adding a strengthening phase Ni to the aluminum bronze matrix. 3 Al and composite lubricating phase (CeF 3 +Ag), and accurately regulate Ni 3 Al and (CeF 3 +Ag) content, realizes the coupling of lubrication and anti-friction performance under high temperature conditions. Compared with materials containing only one additive phase, the present invention enables the material to have both higher strength and lower friction coefficient and wear rate.
[0022] (5) The composite lubricating phase (CeF 3 +Ag) by CeF 3 The powder and Ag powder were prepared by high energy ball milling. 3 The mass ratio of Ag powder and Ag powder and the high-energy ball milling process were obtained through multiple experiments, which can improve the uniformity and surface chemical energy of the composite lubricating phase, making it easier to closely combine with the high manganese aluminum bronze interface and distribute evenly during hot pressing sintering.
[0023] (6) The present invention provides a method for preparing a wear-resistant self-lubricating friction material in a high temperature environment. In the preparation method, high manganese aluminum bronze matrix powder, Ni 3 Al powder and (CeF 3 + Ag) powder is ball-milled under the protection of inert gas, and the obtained mixed powder is placed in a sintering furnace for hot pressing and sintering, and then cooled in the furnace after sintering. Compared with the existing preparation technology, the preparation process of the present invention is obtained through multiple experiments, which can improve the uniformity and strength of the material on the one hand, and improve the density and hardness on the other hand.
[0024] (7) The material of the present invention has high hardness, compressive strength and flexural strength, and has low wear rate and low and stable friction coefficient under high temperature conditions, and has good anti-friction and anti-wear properties. At the same time, the material preparation method is simple, the raw materials used are environmentally friendly, the preparation cost is low, and it has broad application prospects in the fields of electricity, energy, corrosive environment and rail transportation. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with specific embodiments, wherein the methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified.
[0026] Example 1
[0027] 20.0 g of CeF 3 The powder and 80.0 g of Ag powder were added into a ball mill (WC-Co hard alloy ball mill), and ball mill beads (WC-Co hard alloy ball mill beads) were added according to the ball-to-material ratio of 3:1. 1 mL of anhydrous ethanol was added, and the ball mill speed was set to 250 r / min. Ball milling was performed under an argon protective atmosphere. The ball milling was stopped every 10 min, and the ball milling was continued after stopping for 2 min. The ball milling was performed for 8 h to obtain CeF 3 The composite lubricating phase (i.e. CeF 3 +Ag);
[0028] 73.0g of Cu powder, 6.0g of Al powder, 1.0g of Ni powder, 2.5g of Fe powder, 8.5g of Mn powder, 0.5g of Co powder, 0.5g of B powder, 3.0g of Ni3 Al powder and 5.0 g (CeF 3 +Ag) composite lubricating phase is added into a ball mill (WC-Co hard alloy ball mill), ball milling beads (WC-Co hard alloy ball milling beads) are added according to a ball-to-material ratio of 2:1, the ball milling speed is set to 170r / min, and ball milling is performed under an argon protective atmosphere for 6h to obtain a mixed raw material;
[0029] The mixed raw materials are first loaded into a graphite mold and then transferred to a spark plasma sintering furnace for hot pressing sintering under a vacuum degree below 0.1 Pa. The temperature is raised to 850°C at a heating rate of 110°C / min, and a sintering pressure of 36 MPa is applied. The mixture is sintered at 850°C and 36 MPa for 5 minutes, and then cooled to room temperature with the furnace to obtain a wear-resistant and self-lubricating copper-based friction material in a high temperature environment.
[0030] The performance test of the friction material prepared in Example 1 was carried out: the density was measured by Archimedes principle and was 7.39 g / cm 3 The hardness of the steel sheet was tested by a Vickers hardness tester and was found to be 190 HV. The mechanical properties were tested by a CMT-5205 universal material testing machine with a compression and three-point bending displacement rate of 0.1 mm / min. The average compressive strength was measured to be 1026 MPa and the average bending strength was 842 MPa.
[0031] The high temperature tribological properties of the friction material prepared in Example 1 were evaluated using a HT-1000 high temperature friction and wear tester. The dual ball was 316 stainless steel (diameter 4 mm, surface roughness 0.02), the load was 10 N, the sliding speed was 0.15 m / s, the friction radius was 5 mm, the running time was 30 min, and the test temperature was 20°C and 550°C. The test showed that the average friction coefficient of the friction material at 20°C was 0.28, and the average wear rate was 1.8×10 -4 mm 3 / N·m; the average friction coefficient at 550℃ is 0.51, and the average wear rate is 4.5×10 -4 mm 3 / N·m, with good anti-friction and anti-wear properties.
[0032] Example 2
[0033] 50.0 g of CeF 3 The powder and 50.0 g of Ag powder were added into a ball mill (WC-Co hard alloy ball mill), and ball mill beads (WC-Co hard alloy ball mill beads) were added according to the ball-to-material ratio of 3.5:1. 2 mL of anhydrous ethanol was added, and the ball mill speed was set to 300 r / min. Ball milling was carried out under an argon protective atmosphere. The ball milling process was stopped every 8 min, and the ball milling was continued after stopping for 2 min. The ball milling was carried out for 9 h to obtain CeF3 The composite lubricating phase (i.e. CeF 3 +Ag);
[0034] 64.5g of Cu powder, 8.0g of Al powder, 2.5g of Ni powder, 3.0g of Fe powder, 6.0g of Mn powder, 1.0g of Co powder, 1.0g of B powder, 6.0g of Ni 3 Al powder and 8.0 g (CeF 3 +Ag) composite lubricating phase is added into a ball mill (WC-Co hard alloy ball mill), ball milling beads (WC-Co hard alloy ball milling beads) are added according to a ball-to-material ratio of 3:1, the ball milling speed is set to 180r / min, and ball milling is performed under an argon protective atmosphere for 8h to obtain a mixed raw material;
[0035] The mixed raw materials are first loaded into a graphite mold and then transferred to a spark plasma sintering furnace for hot pressing sintering under a vacuum degree below 0.1 Pa. The temperature is raised to 880°C at a heating rate of 140°C / min, and a sintering pressure of 38 MPa is applied. The mixture is sintered at 880°C and 38 MPa for 10 minutes, and then cooled to room temperature with the furnace to obtain a wear-resistant and self-lubricating copper-based friction material in a high temperature environment.
[0036] The performance test of the friction material prepared in Example 2 was carried out: the density was measured by Archimedes principle and was 7.38 g / cm 3 ; The average hardness of the steel sheet was tested by a Vickers hardness tester and was found to be 197 HV; the mechanical properties were tested by a CMT-5205 universal material testing machine, with a compression and three-point bending displacement rate of 0.1 mm / min, and the average compressive strength was measured to be 972 MPa and the average bending strength was 826 MPa.
[0037] The high temperature tribological properties of the friction material prepared in Example 2 were evaluated using a HT-1000 high temperature friction and wear tester. The dual ball was 316 stainless steel (diameter 4 mm, surface roughness 0.02), the load was 10 N, the sliding speed was 0.3 m / s, the friction radius was 5 mm, the running time was 30 min, and the test temperature was 20°C and 550°C. The test showed that the average friction coefficient of the friction material at 20°C was 0.24, and the average wear rate was 1.6×10 -4 mm 3 / N·m; the average friction coefficient at 550℃ is 0.46, and the average wear rate is 4.1×10 -4 mm 3 / N·m, with good anti-friction and anti-wear properties.
[0038] Example 3
[0039] 80.0 g of CeF3 The powder and 20.0 g of Ag powder were added into a ball mill (WC-Co hard alloy ball mill), and ball mill beads (WC-Co hard alloy ball mill beads) were added according to the ball-to-material ratio of 4:1. 3 mL of anhydrous ethanol was added, and the ball mill speed was set to 350 r / min. Ball milling was performed under an argon protective atmosphere, and the ball milling was stopped every 5 min. After stopping for 3 min, the ball milling was continued for 10 h to obtain CeF 3 The composite lubricating phase (i.e. CeF 3 +Ag);
[0040] 58.0g of Cu powder, 6.0g of Al powder, 1.0g of Ni powder, 2.0g of Fe powder, 10.0g of Mn powder, 0.5g of Co powder, 0.5g of B powder, 10.0g of Ni 3 Al powder and 12.0 g (CeF 3 +Ag) composite lubricating phase is added into a ball mill (WC-Co hard alloy ball mill), ball milling beads (WC-Co hard alloy ball milling beads) are added according to a ball-to-material ratio of 3:1, the ball milling speed is set to 200r / min, and ball milling is performed under an argon protective atmosphere for 9h to obtain a mixed raw material;
[0041] The mixed raw materials are first loaded into a graphite mold and then transferred to a spark plasma sintering furnace for hot pressing sintering under a vacuum degree below 0.1 Pa. The temperature is raised to 910°C at a heating rate of 170°C / min, and a sintering pressure of 40MPa is applied. The mixture is sintered at 910°C and 40MPa for 5 minutes, and then cooled to room temperature with the furnace to obtain a wear-resistant and self-lubricating copper-based friction material in a high temperature environment.
[0042] The performance test of the friction material prepared in Example 3 was carried out: the density was measured by Archimedes principle and was 7.37 g / cm 3 ; The average hardness of the steel sheet was tested with a Vickers hardness tester and was found to be 208 HV; the mechanical properties were tested using a CMT-5205 universal material testing machine, with a compression and three-point bending displacement rate of 0.1 mm / min, and the average compressive strength was measured to be 920 MPa and the average flexural strength was 765 MPa.
[0043] The high temperature tribological properties of the friction material prepared in Example 3 were evaluated using a HT-1000 high temperature friction and wear tester. The dual ball was 316 stainless steel (diameter 4 mm, surface roughness 0.02), the load was 10 N, the sliding speed was 0.3 m / s, the friction radius was 5 mm, the running time was 30 min, and the test temperature was 20°C and 550°C. The test showed that the average friction coefficient of the friction material at 20°C was 0.19, and the average wear rate was 1.4×10 -4 mm 3 / N·m; the average friction coefficient at 550℃ is 0.39, and the average wear rate is 3.7×10 -4 mm 3 / N·m, with good anti-friction and anti-wear properties.
[0044] Comparative Example 1
[0045] Compared with Example 1, the Mn content in Comparative Example 1 is reduced, and Co and B elements are not added. The specific composition of the material is: 77.5g of Cu powder, 8.0g of Al powder, 2.5g of Ni powder, 3.0g of Fe powder, 1.0g of Mn powder, 3.0g of Ni 3 Al powder, 5.0 g (CeF 3 +Ag) powder. The other preparation process and process parameters are the same as those in Example 1. The material properties obtained in Comparative Example 1 are compared with those in Example 1 (Table 1). The results show that the hardness and compressive strength of Comparative Example 1 decrease, and the wear rate increases. This is because the lack of Mn, Co, and B elements cannot produce fine grain strengthening and dispersion strengthening, resulting in a decrease in the hardness and strength of the material, which in turn causes a decrease in wear resistance.
[0046] Table 1 Comparison of Comparative Example 1 with Example 1
[0047]
[0048] Comparative Example 2
[0049] Compared with Example 2, Comparative Example 2 strengthens the Ni 3 Al is replaced by the commonly used strengthening phase Al 2 O 3 , the mass is the same as 6.0g. The other material components, contents, and preparation processes are consistent with those in Example 2. The material properties obtained in Comparative Example 2 are compared with those in Example 2 (Table 2). The results show that the compressive strength and flexural strength of Comparative Example 2 decrease, and the wear rate increases. This is due to the Al 2 O 3 The interfacial bonding strength with high manganese aluminum bronze is lower than that of Ni 3 The interfacial bonding force between Al and high manganese aluminum bronze causes the material strength to decrease, and the material is more likely to peel off from the surface during friction, so the wear resistance is reduced.
[0050] Table 2 Comparison of Comparative Example 2 with Example 2
[0051]
[0052] Comparative Example 3
[0053] Compared with Example 3, Comparative Example 3 adds the composite lubricating phase (CeF 3+Ag) was replaced with common lubricating phase graphite, with the same mass of 12.0g. The other material components, contents, and preparation processes were consistent with those in Example 3. The material properties obtained in Comparative Example 3 were compared with those in Example 3 (Table 3). The results showed that the friction coefficient and wear rate of Comparative Example 3 increased at 550°C. This is because CeF 3 It has excellent lubrication performance, while graphite is not as good as CeF in high temperature environment. 3 , resulting in an increase in the friction coefficient and aggravated wear of Comparative Example 3.
[0054] Table 3 Comparison of Comparative Example 3 with Example 3
[0055]
[0056] Comparative Example 4
[0057] Compared with Example 2, Comparative Example 4 adds the composite lubricating phase (CeF 3 +Ag) was replaced by pure CeF 3 , with a mass of 8.0 g. Other material components, contents, and preparation processes are consistent with those of Example 2. The material properties obtained in Comparative Example 4 are compared with those in Example 2 (Table 4). The results show that the compressive strength and flexural strength of Comparative Example 4 decrease. This is due to the CeF 3 The interface bonding strength between CeF and high manganese aluminum bronze is lower than that between Ag and high manganese aluminum bronze. 3 When the content of is too high, cracks are likely to initiate and propagate at the grain boundaries of the material, resulting in a decrease in strength.
[0058] Table 4 Comparison of Comparative Example 4 with Example 2
[0059]
[0060] Comparative Example 5
[0061] Compared with Example 2, Comparative Example 5 adds the composite lubricating phase (CeF 3 +Ag) was replaced by pure Ag, with a mass of 8.0g. The other material components, contents, and preparation processes were consistent with those in Example 2. The material properties obtained in Comparative Example 5 were compared with those in Example 2 (Table 5). The results showed that the friction coefficient and wear rate of Comparative Example 5 increased at 550°C. This is because the lubricating effect of Ag is weaker than that of CeF in a high temperature environment. 3 , when the material does not contain CeF 3 Afterwards, the lubrication ability decreases at high temperatures, resulting in an increase in the friction coefficient and increased wear.
[0062] Table 5 Comparison of Comparative Example 5 with Example 2
[0063]
[0064]
[0065] Comparative Example 6
[0066] Compared with Example 3, in the preparation of (CeF 3 +Ag) powder was not subjected to high-energy ball milling, and the sintering temperature was higher than the specified range and the sintering pressure was lower than the specified range when the composite material was prepared by hot pressing sintering. 3 +Ag) powder is prepared as follows: 80.0 g of CeF 3 Powder and 20.0g of Ag powder are added to a ball mill, and grinding balls are added according to a ball-to-material ratio of 1:1. The ball mill speed is set to 150r / min and the ball mill is milled for 5h. The hot pressing sintering process of the composite material is as follows: the temperature is increased to 960°C at a heating rate of 110°C / min, and a pressure of 20MPa is applied. After keeping the temperature at 960°C and 20MPa for 5min, the furnace is cooled to room temperature. The other material components, contents, and preparation processes are consistent with those in Example 3.
[0067] The performance of the material obtained in Comparative Example 6 is compared with that in Example 3 (Table 6). The results show that the strength of the material obtained in Comparative Example 6 decreases and the wear rate increases. This is because the Comparative Example 6 is prepared (CeF 3 +Ag) powder was not subjected to high-energy ball milling, resulting in (CeF 3 +Ag) powder composition is uneven and the surface chemical energy is low, and the bonding strength with the aluminum bronze matrix decreases after being added. At the same time, the sintering temperature of comparative example 6 is too high, resulting in component segregation of aluminum bronze, and the α phase and κ phase formed by Cu and Al are uneven, and the sintering pressure of comparative example 6 is too low, resulting in a decrease in the hardness and strength of the material.
[0068] Table 6 Comparison of Comparative Example 6 with Example 3
[0069]
[0070] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. High temperature environment wear-resistant self-lubricating copper-based friction material, characterized by: Taking the total mass of the raw materials for preparing the friction material as 100%, the composition of the raw materials and the mass percentage of each component are as follows: high manganese aluminum bronze 78-92%, Ni3Al 3-10%, and composite lubricating phase 5-12%; Wherein, the composite lubricating phase is a composite of CeF3 and Ag; The components of the high manganese aluminum bronze and the mass percentage of each component in the raw material for preparing the friction material are as follows: Cu 58-73%, Al 6-8%, Ni 1-2.5%, Fe 2-3%, Mn 6-10%, Co 0.5-1%, and B 0.5-1.0%.
2. The high temperature environment wear-resistant self-lubricating copper-based friction material according to claim 1, characterized in that: The particle size of the single substance powders of Cu, Al, Ni, Fe, Mn, Co and B is 200-300 mesh.
3. The high temperature environment wear-resistant self-lubricating copper-based friction material according to claim 1, characterized in that: The mass ratio of CeF3 to Ag in the composite lubricating phase is 20:80-80:
20.
4. The high temperature environment wear-resistant self-lubricating copper-based friction material according to claim 1 or 3, characterized in that: The composite lubricating phase is obtained by mixing CeF3 and Ag by high-energy ball milling under the protection of inert gas, wherein the ball-to-material ratio is 3:1-4:1, the ball milling speed is 250-350r / min, the ball milling time is 8-10h, anhydrous ethanol is added before ball milling, the ball milling is stopped every 5-10min, and the ball milling is continued after stopping for 2-3min.
5. The method for preparing the wear-resistant self-lubricating copper-based friction material in a high temperature environment according to any one of claims 1 to 4, characterized in that: The following steps are involved: Firstly, high manganese aluminum bronze, Ni3Al and a composite lubricating phase are uniformly mixed to obtain a mixed raw material; the mixed raw material is loaded into a sintering mold, and then placed in a sintering furnace for sintering to obtain the friction material.
6. The method for preparing the high temperature environment wear-resistant self-lubricating copper-based friction material according to claim 5, characterized in that: Under an inert gas protective atmosphere, a ball milling mixing method is used to obtain the mixed raw materials, the ball-to-material ratio is 1:1-3:1, the ball milling speed is 150-200 r / min, and the ball milling time is 6-9 h.
7. The method for preparing the high temperature environment wear-resistant self-lubricating copper-based friction material according to claim 5, characterized in that: The sintering process parameters are as follows: hot pressing sintering is carried out under a vacuum degree lower than 0.1 Pa, the sintering temperature is 850-910° C., the sintering pressure is 36-40 MPa, and the sintering heat preservation and pressure holding time is 5-10 min.
8. The method for preparing the wear-resistant self-lubricating copper-based friction material in a high temperature environment according to claim 5, characterized in that: The heating rate during the sintering process is 110-170°C / min.
Citation Information
Patent Citations
Switch capable of preventing arc
CN108417435A
Rare-earth-doped aluminum bronze and preparation method thereof
CN112195361A
A high-strength, wear-resistant, deformable aluminum bronze alloy
CN102296206A
Copper-aluminum-iron-nickel-manganese-chromium-silicon alloy capable of improving wear-resistant performance
CN105088004A